Competing Temperature and Atmospheric Circulation Effects on Southwest Madagascan Rainfall During the Last Deglaciation. Issue 2 (27th February 2019) - Scroxton, Nick; Burns, Stephen J.; McGee, David; Hardt, Ben; Godfrey, Laurie R.; Ranivoharimanana, Lovasoa; Faina, Peterson
Abstract: The global paleomonsoon concept predicts an antiphase response of monsoon rainfall in the Northern and Southern Hemispheres at timescales where there is asymmetric solar forcing and/or asymmetric hemispheric temperature changes. However, as different monsoon systems have different sensitivities to local, regional, and global forcing, rainfall response may vary regionally, particularly during large global climatic changes such as the last deglaciation where warming occurred in both hemispheres. Despite its role as a key Southern Hemisphere counterpart to the Arabian and Indian summer monsoons, the behavior of the summer monsoon in the Southern Hemisphere of the Indian Ocean during the last deglaciation is unknown. Therefore, we present a new high‐resolution, precisely dated, and replicated speleothem stable isotope record from Tsimanampesotse National Park in southwest Madagascar that covers the last deglaciation. We show that speleothem growth phases respond largely to movements of the Southern Hemisphere summer Hadley circulation (summer extent of the tropical rainbelt/mean Intertropical Convergence Zone location), with some contribution from sea surface temperature changes at key times, such as during the Bølling‐Allerød. In contrast, speleothem δ 18 Ο responds primarily to sea surface temperature, in particular the location of the deep atmospheric convection isotherm, while summer Hadley circulation changes take a secondary role. Separating the varying influences of temperature and atmospheric circulation in controlling southwest Madagascan rainfall is critical to understanding rainfall variability in both the past and the future. Plain Language Summary: Understanding how monsoon rainfall might change under a changing climate is important to ensure the water supply for millions of people who depend on monsoon rainfall. Despite this, how Southern Hemisphere monsoon systems such as the Madagascan summer monsoon varied in the past are not well understood. We use stalagmites from Tsimanampesotse National Park in southwest Madagascar to create a new record of past changes in monsoon rainfall in the region. We use the timing of stalagmite growth and the stable isotopes of these stalagmites to reveal a series of wet and dry periods during the last deglaciation, a time of rapid climate change. Our new record shows that variability in monsoon rainfall is dependent on both temperature and atmospheric circulation changes. Both southward shifts in the tropical rainfall belt and warmer sea surface temperatures contributed to periods of higher rainfall in southwest Madagascar. Our rainfall sensitive site is able to detect changes in the monsoon that correspond to millennial‐ and centennial‐scale climatic events in the Northern Hemisphere, indicating links with the global tropical monsoon system. Key Points: Speleothem growth and stable isotopes in southwest Madagascar controlled by sea surface temperature and summer Hadley circulation movement Speleothem δ 18 Ο follows a threshold response to sea surface temperatures above/below the deep atmospheric circulation isotherm Second order speleothem δ 18 Ο variability antiphase to northern hemisphere monsoon records, consistent with the global paleomonsoon concept